Exploring Online Preferences of Pakistani Adolescents with reference to their Gender and Age Group - Saleem, Kiran; Rauf, Nelofar Kiran (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore online preferences of Pakistani adolescents with reference to their gender and age group.Study Design: Qualitative study (Interpretive Paradigm)Place and Duration of Study: National Institute of Psychology, Quaid-i-Azam University, Islamabad Pakistan, from Nov 2020 to Jan 2021.Methodology: To explore online preferences of Pakistani adolescents, eight online focus group discussions (FGDs) were conducted. Four of the FGDs were carried out with adolescents (13-19 years) and the remaining four were conducted with parents of adolescents. Data was transcribed and results were calculated employing content analysis.Results: Online preferences among adolescents of Pakistan were shared in terms of frequently used internet applications, during FGDs. All the shared applications were grouped into four major categories and top three most frequently used applications under each category were found as follow.1 Applications used for educational purpose: {i. Google/Wikipedia, ii. MS Teams, iii. Zoom}.2. Applications used for recreational purpose: {i. YouTube, ii. Netflix, iii. SoundCloud}.3 Applications for communication purpose: {i. WhatsApp, ii. Instagram, iii. Facebook}.4. Online gaming {i. PUBG & Online Sports (Cricket, Fifa, Ludo etc.) ii. Among US & Call of Duty, iii. Grand Theft Auto}. Considerable, gender and age-related differences were also identified for the online preferences of adolescents.Conclusion: The study provides insight regarding online preferences among adolescents of Pakistan and highlights the need of further inquiry as well as effective interventions